2001
DOI: 10.1007/s004420100697
|View full text |Cite
|
Sign up to set email alerts
|

Which functional processes control the short-term effect of grazing on net primary production in grasslands?

Abstract: Grazing has traditionally been viewed as detrimental to plant growth, but it has been proposed that under certain conditions, grazing may lead to compensatory or overcompensatory growth. However, comprehensive information on the relative role of the main functional processes controlling the response of net primary production (NPP) to grazing is still lacking. In this study, a modelling approach was used to quantify the relative importance of key functional processes in the response of annual canopy NPP to graz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 63 publications
5
66
0
1
Order By: Relevance
“…The lower LSR on pasture managed with lower height (15 cm) in the winter compared with the pasture maintained at 25 cm height can be attributed to more intensive grazing management in the first condition, which provided greater removal of not synthetically active tissues and, indeed, it may have increased the photosynthetic rate of the pasture (Leriche et al, 2001). Thus, the lower pasture in the winter probably had lower negative energy balance, which explains their lower LSR.…”
Section: Resultsmentioning
confidence: 98%
“…The lower LSR on pasture managed with lower height (15 cm) in the winter compared with the pasture maintained at 25 cm height can be attributed to more intensive grazing management in the first condition, which provided greater removal of not synthetically active tissues and, indeed, it may have increased the photosynthetic rate of the pasture (Leriche et al, 2001). Thus, the lower pasture in the winter probably had lower negative energy balance, which explains their lower LSR.…”
Section: Resultsmentioning
confidence: 98%
“…For carbon sequestration, some studies found that grazing exclusion facilitated vegetation recovery, increased plant productivity and thus enhance soil carbon stocks in degraded grasslands (Biondini et al, 1998;McIntosh and Allen, 1998;Li et al, 2008;Mekuria et al, 2007;Mekuria and Veldkamp, 2012;Xiong et al, 2014). Others, however, reported no change (McNaughton et al, 1998;Pucheta et al, 2004) or even decline of carbon stocks in grasslands (Schuman et al, 1999;Leriche et al, 2001;Frank et al, 2002;Wienhold et al, 2001). Controversial results have also been found on a regional and global scale.…”
Section: Introductionmentioning
confidence: 99%
“…Negative effects can also be observed in nutrient-poor systems or under high grazing pressure (Bardgett and Wardle, 2003). Because N is the limiting factor for primary production in many ecosystems (Vitousek and Howarth, 1991), grazing-induced enhancement of soil N dynamics is a key mechanism through which herbivores can influence plant productivity in such a way as to alleviate nutritional deficiencies (McNaughton et al, 1997;Leriche et al, 2001). In particular, the regulation of nitrification has often been regarded as the key for an efficient nitrogen cycling in this context, as in contrast to most other steps in nitrogen turnover only a limited number of microbes is able to convert ammonia into nitrate.…”
Section: Introductionmentioning
confidence: 99%